Feasibility of Establishing Descriptive Evaluation and its Benefits in Secondary Schools of Iran - Milad Moradi Behpour; Soolmaz Nourabadi (International Journal of Supply Chain Management, 2020)
Abstract. The purpose of this study is to assess the feasibility of establishing descriptive evaluation and its use in secondary school from the perspective of secondary school’s teachers in Hamadan. Basically, in order to evaluate the achievement of students in schools, used two methods of quantitative evaluation and descriptive evaluation. The quantitative evaluation follows the principles of classical psychology and behaviorism, while the descriptive evaluation follows the principles of constructivist psychology. The method of this research is descriptive and survey type. The statistical population includes all 577 secondary school teachers in Hamadan, of which 234 were selected by stratified random sampling method. In order to assess the feasibility, five components were considered includes human, structural, technological, temporal, and financial. A researcher-made questionnaire with a five-point Likert scale was used to collect information. The validity of tool was confirmed by experts and its reliability was obtained through Cronbach's alpha of 83%. In order to analyze information were used descriptive and inferential statistics. The results showed that in structural component, the studied fields are not provided (submitted circulars, content of books, application of plan in all courses and foundations). In the technological component, there are no hardware and software facilities in secondary schools to implement this plan. In the time component of school year, daily school time and time in classroom are not commensurate with descriptive evaluation plan. The financial component does not provide sufficient budget for implementation of plan. In the human component, education teachers lack of interest and ability to implement this plan.